Determinants of Ethiopian Coffee Exports to its Major Trade Partners: A Dynamic Gravity Model Approach - Eshetu, Fassil; Goshu, Degye (Journal of Asian Business Strategy, 2019)
The aim of this paper was to examine export determinants of Ethiopian coffee to 31 trade partners’ countries. The export determinants were examined using a dynamic gravity model and system generalized moment method of estimation from a year 1998-2016. The results of the descriptive analysis showed that Ethiopia was ranked fifth in terms of production and exports of coffee in the world and was also exporting only 39% of its total coffee production. On average, 53.5 and 34.13 percent of Ethiopian coffee exports were directed to European and Asian countries respectively over the period 1998-2016. The regression result of system generalized moment method revealed that trade openness, population size of Ethiopia, foreign direct investment and institutional quality index of Ethiopia has positively and significantly affected the volume of Ethiopian coffee export. But, population of partner countries, weighted distance, lagged export volume and real exchange rate had negatively and significantly influenced the export volume of Ethiopian coffee. Hence, Ethiopia needs to diversify its export destinations and export items a way from primary products to secondary products in order to secure dependable source of foreign currency. As well, improving the institutional quality, promotion of foreign direct investment and swelling trade liberalization would help to boost the volume of Ethiopian coffee export.